Analisis Biaya Standar Sebagai Alat Perencanaan Dan Pengendalian Biaya Produksi Pada UMKM - Hasibuan, Ahmad Nurdin; Fauziyah, Hanifah; Sitorus, Imran Riadi; Fauzi, Achmad; Prastia, Geby Ari; Novianto, Irvan; Thoriqin, Azis (OGZ Research & Publishing, 2024)
When carrying out production activities in a company, the process will not be overlooked. Overall, the production process begins by determining the final production results, in this case an information media-based company the company will determine the form of news and information that will be produced. The research include the qualitative and descriptive research, aimed at describing, summarizing various conditions or various phenomena of social reality that exist in companies which are the object of research related to standard cost analysis as a planning tool for controlling production costs in MSMEs. The source of data used in this research is secondary data sourced from journals and other supporting articles such as standard costs in planning and controlling production costs. Data collection methods use interviews and documentation. The qualitative descriptive method will be used as the Analysis method to discussing the problems by collecting, describing, calculating and comparing a situation and explaining a situation so that conclusions can be drawn which include standard cost analysis as a one of planning tool for controlling the production costs in MSMEs. Enhanced competitiveness: By improving the production understanding and calculations, MSMEs can increase their competitiveness in the market. By optimizing the operations and producing the products of good quality, MSMEs can also attract more customers, retain the existing customers, and compete with other MSMEs in the bag industry. This can help MSMEs expand their market reach, increase revenue and achieve sustainable growth.Keywords: Cost Control, Standard Cost Analysis.